Optimization of Disinfection of Raw Wheat Sprout by Combination of Ultrasonic and Citric Acid Using Response Surface Methodology (RSM) - Maryam Safarirad; Fatemeh Hemmati; Sara Jafari; Enayat Berizi; Azam Abbasi (Journal of Food Quality, 2025)
This study investigated the synergistic effects of ultrasound (US) and citric acid (CA) on the microbial load and chemical quality of raw wheat sprouts, leveraging a nonthermal approach for food safety enhancement. Here, we aimed to optimize the application of combined US and CA treatments to reduce the microbial load as much as possible while preserving the desirable chemical attributes of wheat sprouts. A central composite design (CCD) within the framework of the response surface methodology (RSM) enabled the modeling and optimization of the process parameters. Twenty wheat sprout samples were treated according to an experimental design generated by design-expert software, using an ultrasonic probe immersed in each sample container. The treatments varied in ultrasonic power (25%, 50%, and 75%), exposure time (5, 7.5, and 10 min), and CA concentration (0%, 0.5%, and 1%). All samples, including a control, were subjected to microbial analysis (total microbial count, coliforms, molds, and yeasts) and chemical analysis. Each experiment was conducted in triplicate. The combined US–CA treatment significantly reduced microbial loads, achieving reductions of 4.92, 2.58, and 1.26 log CFU/g for coliforms, molds and yeasts, and total microbial count, respectively. The optimized treatment, which involved a low CA concentration of 0.5%, effectively improved the microbial quality of raw wheat sprouts, bringing them within acceptable safety limits. These findings indicated that the combined application of US and CA is a promising approach for disinfecting wheat sprouts and enhancing their food safety.